Amelioration of hepatic fibrosis by NK cell activation. Issue 1 (26th July 2010) - Muhanna, Nidal; Tair, Lina Abu; Doron, Sarit; Amer, Johnny; Azzeh, Maysa; Mahamid, Mahmud; Friedman, Scott; Safadi, Rifaat
Abstract : Background and aims: Interactions between hepatic stellate cells (HSCs) and immune cell subsets have emerged as important determinants of liver fibrosis progression and regression. Natural killer (NK) cells have an antifibrotic activity through killing of activated HSCs. In liver injury NK cell expression of activating/inhibitory killer immunoglobulin-related receptors (aKIR/iKIR) and their ratio are significantly increased, while class I major histocompatibilty (MHC) expression by activated HSCs is decreased. The aim of this study was to amplify the antifibrotic activity of NK cells and ameliorate hepatic fibrosis by iKIR silencing. Methods: Human lymphocytes from patients with hepatitis C virus (HCV) infection were transfected with specific iKIR small interfering RNAs (siRNAs) or non-silencing control siRNAs, then co-cultured with a human HSC line and assessed for fibrogenic activity. To induce hepatic fibrosis, carbon tetrachloride was administrated to BALBc SCID-Beige male mice (lacking B/T/NK cells) for 4 weeks. Splenocytes from naive SCID donors (lacking B/T cells but with preserved NK cells) were transfected in vitro with either iKIR siRNA or non-silencing control siRNA, and then were transferred to the fibrotic SCID-Beige recipients. Results: Transfection with iKIR or positive control siRNAs (mice and human) decreased mRNA expression of iKIR and mitogen-acivated protein kinase 1 (MAPK1). Consequently, total NK cells and NK cell degranulation were increased (p=0.01), consistent with NK cell stimulation. Compared with healthy lymphocytes, when HCV lymphocytes were transfected with non-silencing control siRNA and co-cultured with HSCs there was increased α-smooth muscle actin (αSMA) expression, reflecting HSC activation. Expression of αSMA in co-cultures was attenuated when HCV lymphocytes were transfected with iKIR siRNA. In SCID-Beige recipients, hepatic fibrosis and serum alanine aminotransferase (ALT) levels were significantly attenuated as a result of receiving iKIR siRNA. Conclusions: iKIR knockdown stimulates NK cells and promotes their antifibrogenic activity in mice and human co-cultures. These findings have implications for possible immune therapeutic strategies in patients with advanced liver disease.